The Pedagogy of Alternation from Different Perspectives: Formation Report with Pedagogy Course Students, CEFFA Monitors, and Educampo Teachers - Alberto Dias Valadão (Universidade Federal do Norte do Tocantins, 2024)
This work aimed to report on the experience of an Extension Course promoted by the Academic Department of Humanities and Social Sciences (DACHS), UNIR, Ji-Paraná Campus, which aimed to provide students of the Pedagogy Course at UNIR, monitors of CEFFA in Ji-Paraná, and teachers from the Educampo project of the municipal education network of Ji-Paraná with training on Alternating Pedagogy. It also aimed to provide readers with compiled theoretical aspects of Alternating Pedagogy. The methodological procedure adopted was descriptive research. It was considered for the offering of the Course that Pedagogy students have only one 40-hour curricular component addressing Rural Education; monitors have not received Alternating Pedagogy training since 2013 from CEFFA and the regional association; Educampo teachers from SEMED have not been trained to work in this educational modality. The Course had 58 participants and was conducted in 10 sessions of 4 hours each. It is noted through excerpts from the memorial, used as an evaluative action of the Course, that this educational proposal promotes a pedagogical practice based on everyday social experiences, becoming a means for sustainable and collective regional development of those involved.